(untitled) (American Journal of Environment and Climate, 2022)
In microbial fuel cell technology, the substrate is consumed by microbes in anaerobic conversion of substrate to electricity. Bio-remediation of pollutants involves microbial environmental cleanup using green approach. The primary problems with pesticides are linked to the non-negligible proportion of the sprayed active ingredient that does not reach its intended target thereby contaminating environmental compartments persistently. The primary objective of this study was to assess the potential of microbial fuel cell technology in bio-remediation of lambda cyahlothrin, chlorpyrifos and malathion in Limuru loam soil. H-shaped double chamber microbial fuel cell was fabricated where the anodic chamber was loaded with 750 mL loam soil inoculated with 750 mL bio-slurry doped with 10 mL of 10 ppm lambda cyhalothrin, chlorpyrifos and malathion pesticide solutions. The cathodic chamber was loaded with 1500 mL distilled water. The setup was incubated for a 90 days retention time where voltage and current were recorded daily using a multi-meter. The degradation level was assessed using a GC-MS after sample extraction using standard QuEChERs method. The voltage generated from the pesticide doped loam soil showed an upward trend from day 0 to day 15 in lambda cyhalothrin and malathion and from day 0 to day 20 in chlorpyrifos and pesticide mixture after which constant readings were observed for three days with downward trends thereafter. The maximum generated voltage was 0.537 V, 0.571 V, 0.572 V and 0.509 V in chlorpyrifos, lambda cyhalothrin, malathion and pesticide mix (MCL) respectively. The bioremediation levels for chlorpyrifos and malathion were 65.80 % and 71.32 %, respectively while no detectable, lambda cyhalothrin was observed after day 60 of the study. This study concludes that bioremediation of lambda cyhalothrin, chlorpyrifos and malathion in Limuru loam soil can be achieved using microbial fuel cells.